Foreign and domestic private investment in developing and emerging economies: A review of literature - Josephine Ofosu-Mensah Ababio; Anthony Q. Q. Aboagye; Charles Barnor; Samuel Kwaku Agyei (Cogent Economics & Finance, 2022)
This study surveys and synthesizes the literature on foreign and domestic private investment over the period 1980-2022 with evidence from developing and emerging economies. The documentary sources method was used to examine one hundred and forty (140) peer-reviewed articles (selected based on source, journal of publication, database, time frame, relevance language, geographical restrictions, and search descriptions) published in a broad range of internationally recognized journals, with special analytical focus placed on forty (40) recent articles. It provides fresh evidence that literature on overall private investment and that of foreign direct investment have been given paramount interest and attention, but domestic private investment has received relatively diminutive attention to date. This review will serve as a roadmap, indicating the current state, contributions made, and unsolved issues in the extant studies as well as situating works to enrich the literature. It, therefore, offers specific directions for researchers, academics, and practitioners.
Keywords: 330; developing and emerging economies; domestic private investment; economic growth; foreign direct investment; private investment